ANALISIS KARAKTERISTIK KEUANGAN TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN INDUSTRY CONSUMER GOODS - Bella Imas Diovany; Dyah Ani Pangastuti (Jurnal Akuntansi dan Perpajakan, 2020)
The aim of the study was to obtain empirical evidences about the effect of cash ratio, debt to equity ratio (DER), return on asset (ROA), asset growth and firm size  on the dividend payout ratio (DPR). The study was designed quantitatively by using the financial report of the companies listed in the Indonesia Stock Exchange, by involving 6 companies listed in the Indonesia Stock Exchange during the period 2010-2015 during six years as the samples, which were selected based on purposive sampling technique. That 36 of company’s data were obtained. The data were analyzed by using multiple linear regression supported by SPSS version 16. The results indicated that: Cash Ratio and Asset Growth had a negative effect and  not significantly on Dividend Payout Ratio (DPR), while the result analysis Debt to Equity Ratio (DER) and Firm Size had a positive effect and significantly on Dividend Payout Ratio (DPR), and Return On Asset had a positive effect and significantly on the Dividend Payout Ratio (DPR). DOI: 10.26905/ap.v6i2.4596